Strategies for Equalizing Educational Access and Social Justice for Underprivileged Communities in Indonesia - Danurwendo, Yudha Suryanjaya; Haryanto, Sigit (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study examines strategies for equalizing educational access and promoting social justice for underprivileged communities in Indonesia through a qualitative approach and a literature review method. The research background highlights disparities in educational access due to high costs, geographical inequalities, and weaknesses in the implementation of government assistance policies. The literature review involved 15 journal articles published between 2020-2024, covering themes such as educational inequality, affirmative policies, and the concept of social justice in education. Descriptive-qualitative analysis reveals that although programs such as KIP (Indonesia Smart Card) and BOS (School Operational Assistance) have been implemented, challenges in distribution and data verification continue to hinder equality. Proposed strategies include strengthening community-based affirmative programs, decentralizing assistance policies, integrating social-educational data, improving educational literacy, and fostering cross-institutional partnerships. The findings affirm that educational management models should be oriented toward distributive justice and inclusivity, enabling them to address the economic, cultural, and structural barriers faced by poor communities. This research is expected to contribute theoretically to the sociology of education and provide practical recommendations for policymakers to strengthen educational inclusion for vulnerable groups.